Process of public administration: Islamic perspective - Noor, Abdun (1998)
Following a brief conceptual survey of the processes of Public Administration, identified by experts and main concerns of public administration leading to emergence of New Public Administration movement, the author relates these to concerns of Islam vide Adle and Ehsan. He argues to show similarities in activities under the modern concept of planning in public administration/management with those under the Islamic concept of planning as well as those related to performance, authority structure, leadership, evaluation and accountability with Islamic prescription. - Reproduced
Keywords: Public administration